Article RETRACTED due to manipulation by the authors Exercise for health in old age: Comprehensive review examining the benefits and efficacy of interven-tions - Didi Suryadi; Nugroho Susanto; Eva Faridah; Ribut Wahidi; Y Touvan Juni Samodra; Ahmad Nasrulloh; Mikkey Anggara Suganda; Isti Dwi Puspita Wati; Albadi Sinulingga; Novita Intan Arovah; Julian Dewantara (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The elderly are a growing age group and an integral part of modern society. The aging process brings significant health challenges, and therefore, exercise has an important role to play in maintaining the quality of life and well-being of older adults. This review aims to explore the role of health exercise in older adults, including its benefits, appropriate types of activities, and factors that influence exercise participation in this age group. Health exercise among older adults was the subject of this systematic review, focusing on the benefits and effectiveness of interventions. This study conducted a keyword search ("exercise activity of the elderly" OR "physical activity for the elderly" AND "benefits of exercise in the elderly" OR "effects of exercise in the elderly" AND "effectiveness of health interventions" OR "physical health of the elderly" AND "exercise health intervention" OR "fitness in old age") on databases (ScienceDirect: 1,2011 and PubMed 1,039) following the Preferred Report-ing Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify articles that addressed the benefits and effectiveness of exercise health interventions in the elderly. Following the exclusion criteria, a total of 15 relevant articles were categorized. The review presented the benefits of health exercise in older adults. In the first group, a 12-week moderate-to-high intensity exercise program was shown to improve various aspects of physical and cognitive health in older adults. These included increases in body mass, functional capacity, muscle strength and reduced risk of age-related diseases. The second group highlighted the benefits of exercise through specific sporting activities, with improved sleep, decreased pain perception and protection from death anxiety. In addition, this group also demonstrated the effectiveness of various exercise therapies in supporting healthy aging. In the third group, the implementation of physical activity and lifestyle was shown to be effective in increasing physical activity levels among older adults and helping to prevent decline in physical function. This review highlights the importance of health exercise in improving the health and well-being of older adults. The findings can serve as a foundation for designing more effective interventions to support active and healthy lifestyles among older adults. This comprehensive strategy aims to enhance the overall well-being of the elderly population, fostering a better quality of life and mitigating the impact of age-related ailments. As such, it necessitates an approach that takes into account individual requirements and constraints. Beyond its health advantages, exercise holds significant social implications. Engaging in physical activity facilitates social interaction for older adults, helping them sustain connections with their community, friends, and family, thereby addressing the prevalent issue of social isolation. In this context, the involvement of family, healthcare professionals, and the community plays a pivotal role in supporting the elderly's participation in physical activities. Providing education, assistance, and cultivating a conducive environment for exercise are crucial measures to ensure an optimal quality of life for the elderly demographic.